Les origines de la politique agricole américaine : Croissance et crise en longue période - Berlan, Jean-Pierre (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1981)
The author distinguishes three periods in the analysis of growth of american agriculture for the last hundred years: 1860-1900, expansion based on the conquest of new lands; recession during the twenties and the thirties; since the fourties, new expansion by developping the agro-industrial complex on the basis of soya bean and new highly productive breeding technics. The export of this new model open enlarged solvent markets in and outside the country for american feedgrains and oleaginous. However, just as the USA now attempt to use food as a weapon, american agriculture is confronted with new conditions by intensification of production (increasing costs), saturation of external markets and emergence of new competitors.